Physical Activity, Nutritional Habits, and Sleep Behavior Among Health Profession Students and Employees of a Swiss University During and After COVID-19 Confinement: Protocol for a Longitudinal Observational Study - Rogan, Slavko; Luijckx, Eefje; Taeymans, Jan; Haas, Karin; Baur, Heiner (JMIR Research Protocols, 2020)
BackgroundSARS-CoV-2, a novel coronavirus strain, has resulted in the COVID-19 pandemic since early 2020. To contain the transmission of this virus, the Swiss Federal Council ordered a nationwide lockdown of all nonessential businesses. Accordingly, students and employees of institutions for higher education were informed to continue their academic programs through home-office settings and online lectures. ObjectiveThis longitudinal survey aims to evaluate various lifestyle habits such as physical activity, nutritional habits, and sleep behavior among students and employees of a Swiss University of Applied Sciences during a 2-month period of confinement and social distancing due to the COVID-19 pandemic and 1 year thereafter. MethodsThis paper describes a protocol for a retrospective and prospective observational cohort study. Students and employees of Bern University of Applied Sciences, Department of Health Professions, were invited to anonymously complete a web-based survey during the COVID-19 confinement period. This will be followed by a second survey, scheduled 1 year after the lockdown. Information on various lifestyle aspects, including physical activity, nutritional habits, and sleep behavior, will be collected using adaptations of existing validated questionnaires. ResultsThis longitudinal study started during the government-ordered confinement period in Switzerland in mid-April 2020 and will end in mid-2021. ConclusionsThe findings of this survey will provide information about the impact of confinement during the COVID-19 crisis on the physical activity, nutritional habits, and sleep behavior of students and employees of a Swiss institute. Trial RegistrationClinicalTrials.gov NCT04502108; https://www.clinicaltrials.gov/ct2/show/NCT04502108 International Registered Report Identifier (IRRID)DERR1-10.2196/25051